Emergency single‐balloon enteroscopy in overt obscure gastrointestinal bleeding: Efficacy and safety. Issue 6 (1st December 2014) - Pinto-Pais, Teresa; Pinho, Rolando; Rodrigues, Adélia; Fernandes, Carlos; Ribeiro, Iolanda; Fraga, José; Carvalho, João
Abstract : We aimed to evaluate the impact of emergency single‐balloon enteroscopy (SBE) on the diagnosis and treatment for active overt obscure gastrointestinal bleeding (OGIB). Methods: SBE procedures for OGIB were retrospectively reviewed and sub‐divided according to the bleeding types: active‐overt and inactive‐overt bleeding. The patient's history, laboratory results, endoscopic findings and therapeutic interventions were registered. Emergency SBE was defined as an endoscopy that was performed for active‐overt OGIB, within 24 hours of clinical presentation. Results: Between January 2010 and February 2013, 53 SBEs were performed in 43 patients with overt OGIB. Seventeen emergency SBEs were performed in 15 patients with active overt‐OGIB procedures (group A), which diagnosed the bleeding source in 14: angiodysplasia ( n = 5), ulcers/erosions ( n = 3), bleeding tumors (gastrointestinal stromal tumor (GIST), n = 3; neuroendocrine tumor, n = 1), and erosioned polyps ( n = 2). Endoscopic treatment was performed in nine patients, with one or multiple hemostatic therapies: argon plasma coagulation ( n = 5), epinephrine submucosal injection ( n = 5), hemostatic clips ( n = 3), and polypectomy ( n = 2). Twenty‐eight patients with inactive bleeding (group B) were submitted to 36 elective SBEs, which successfully diagnosed 18 cases. The diagnostic yield in group A (93.3%) was significantly higher than in group B (64.3%)—Fisher's exact test, p = 0.038. Conclusion: This study revealed an important role of emergency SBE in the diagnosis of bleeding etiology in active overt OGIB.